Kopiko Product Placement in Korean Drama on Brand Awareness - Alexandra Bella Ivena; El Chris Natalia (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2023)
Kopiko, one of the products of PT Mayora Indah Tbk appears as a product placement in the Korean drama